ANALYSIS OF ACTS 20:24 AND ITS IMPLICATIONS FOR TRANSFORMATIVE CHRISTIAN EDUCATION - Daniel Ello; Degunias Ton; Dance Otniel Adu; Wilson Simbolon; Yeskiel Sabloit (Jurnal Suluh Pendidikan, 2026)
Christian Religious Education plays a crucial role in shaping students' spirituality, character, and life orientation amidst the challenges of the digital era. However, Christian Religious Education practices still tend to be cognitively oriented and have not optimally integrated service values as the basis for shaping Christian character and lifestyle. On the other hand, research on Acts 20:24 has focused more on the theology of the Apostle Paul's mission and leadership, while its hermeneutical implications for transformative Christian Religious Education are still relatively limited. This study aims to analyze the hermeneutical meaning of Acts 20:24 and its implications for the development of transformative Christian Religious Education. The study used a qualitative document study design through a literature review with a hermeneutical analysis approach. The analysis was conducted through grammatical-historical exegesis of words, phrases, and contexts of Greek texts using BibleWorks and SABDA Bible, then combined with thematic analysis of various biblical theology and Christian Religious Education literature. The results of the study show three main findings. First, Acts 20:24 emphasizes that God's calling is the primary orientation of a believer's life, so Christian Religious Education must shape a Christ-centered identity. Second, Paul's faithfulness in completing his ministry shows that the formation of a spirituality of service needs to be realized through the internalization of values, exemplary behavior, and ongoing service practices. Third, Paul's commitment to preaching the Gospel of God's grace provides a foundation for Christian Religious Education to develop missionary, reflective, and responsible characters in the face of an increasingly individualistic culture. This study emphasizes that Christian Religious Education not only transmits knowledge of faith, but also transforms the spirituality, character, and lifestyle of students through the hermeneutical foundation of Acts 20:24.